From wheat to bread - Nelson, Penelope, 1994- (2021)
"In From Wheat to Bread, early fluent readers learn how bread is made, from wheat being harvested, to it being milled into flour, to baking the bread. Vibrant, full-color photos and carefully leveled text will engage young readers as they learn about how this food gets to their tables. An infographic illustrates the cycle with real photos and descriptions. From Wheat to Bread also features reading tips for teachers and parents, a table of contents, a glossary, and an index"--
"Bullfrog Books are published by Jump!"
Includes index.
Ages 5-8.
Grades K-1.
Keywords: Bread -- Juvenile literature; Wheat -- Juvenile literature